Real-World Evidence for Regulatory Decisions: Concomitant Administration of Zoster Vaccine Live and Pneumococcal Polysaccharide Vaccine. Issue 9 (11th April 2018) - Bruxvoort, Katia; Sy, Lina S; Luo, Yi; Tseng, Hung Fu
Abstract: The US Food and Drug Administration is charged with expanding the use of real-world evidence for regulatory decisions. As a test case for real-world evidence to support regulatory decisions, we present the scenario of concomitant vaccination with zoster vaccine live (ZVL) and 23-valent pneumococcal polysaccharide vaccine (PPSV23). The prescribing information states that these vaccines should not be given concurrently, based on a small trial using varicella zoster virus antibody levels as a correlate of ZVL efficacy, even though ZVL protects against herpes zoster via cell-mediated immunity. We conducted an observational cohort study involving more than 35, 000 members of Kaiser Permanente Southern California receiving concomitant ZVL and PPSV23 versus PPSV23 prior to ZVL. Occurrence of herpes zoster was assessed through electronic health records from January 1, 2007, to June 30, 2016. The adjusted hazard ratio comparing incidence rates of herpes zoster in the concomitant vaccination cohort and the prior vaccination cohort was 1.04 (95% confidence interval: 0.92, 1.16). This real-world evidence study provides direct evidence for a lack of vaccine interference, relying on herpes zoster occurrence rather than an intermediate marker of immunity. Real-world evidence is essential for regulators and policy makers in addressing evidentiary gaps regarding safety, effectiveness, compliance, and vaccine interactions for the new recombinant zoster vaccine.